HUBUNGAN ANTARA CLASSROOM ENVIRONMENT, TEACHER-STUDENT INTERPERSONAL BEHAVIOR, SERTA PRESTASI BELAJAR MAHASISWA PROGRAM STUDI MATEMATIKA [THE RELATIONSHIP BETWEEN THE CLASSROOM ENVIRONMENT AND TEACHER-STUDENT INTERPERSONAL BEHAVIOR ON THE LEARNING ACHIEVEMENT OF MATHEMATICS DEPARTMENT STUDENTS] - Ferdinand, Ferry Vincenttius; Lukas, Samuel (JOHME: Journal of Holistic Mathematics Education, 2020)
Improving learning achievement is an activity that needs to be continuously carried out by an educational institution, and it is necessary to focus on certain areas because of the many things that affect learning achievement. This study focused on the area of the classroom environment and teacher-student interpersonal behavior to see the relationship between each variable with learning achievement, and the relationship between the two variables.  By using a sample of 160 X-university students majoring in mathematics and then using the Chi-Square test method with a contingency table to determine the relationship between each variable and learning achievement. Then using the  Pearson correlation method the relationship between classroom environment with the teacher-student interpersonal behavior was tested. Based on the analysis and calculation of the research conducted, it can be concluded that the classroom environment has a good relationship with learning achievement in the mathematics major and general subjects. Whereas the teacher-student interpersonal behavior shows a positive relationship with learning achievement in the dimensions of leadership, understanding, and friendly/helping but a  negative relationship in the dimensions of strictness and disatisfaction. In the mathematics major, the dimensions of uncertainty and admonishing are negatively related to learning achievement, but not for general subjects.BAHASA INDONESIA ABSTRACT: Meningkatkan prestasi belajar merupakan kegiatan yang masih terus dilakukan dan berkembang, sehingga diperlukan fokus pada area tertentu. Penelitian ini terfokus pada area classroom environment dan teacher-student interpersonal behavior untuk melihat hubungan antara masing-masing variabel dengan prestasi belajar, dan hubungan antara kedua variabel. Penulis mengambil 160 sampel mahasiswa program studi matematika universitas X, kemudian menggunakan metode uji Chi-Square dengan tabel kontingensi akan dilihat hubungan antara masing-masing variabel dengan prestasi belajar. Lalu akan diuji menggunakan metode korelasi r pearson untuk melihat hubungan antara kedua variabel. Dari hasil analisa dan perhitungan penelitian yang dilakukan, dapat diambil kesimpulan Classroom Environment memiliki hubungan dengan prestasi belajar dalam mata kuliah matematika maupun umum. Sedangkan teacher-student interpersonal behavior memperlihatkan hubungan positif dengan prestasi belajar dalam dimensi leadership, understanding, dan friendly/helping serta hubungan negatif dalam dimensi dissatisfied dan strict. Pada mata kuliah matematika, dimensi uncertain dan admonishing berhubungan negatif dengan prestasi belajar, tapi tidak untuk mata kuliah umum.